17 ASSESSING MEDICAL PROFESSIONALS' ATTITUDES CONCERNING CARE AT THE END-OF-LIFE: DEVELOPING AN END-OF-LIFE SELF-EFFICACY SURVEY. (10th December 2015) - Gilmore, E. J.; Forman, W. B.
Abstract : Purpose: To describe and compare the attitudes of family physicians and internists in training and practice regarding perceived self-efficacy in delivering quality end-of-life care. Methods: We created a tool to measure self-efficacy for this cross-sectional survey. Using a five-point Likert scale, we measured physician's attitudes and perceptions of their abilities. An on-line self-administered survey was placed on a secure site, accessible to those selected to participate in the study. All faculty and residents in the departments of Family and Community Medicine and Internal Medicine were considered prospective participants and emailed accordingly (n =340). Measures were self-reported perceptions within four end-of-life care domains (physician's own ability - general, physician's own ability - symptom treatment, crucial areas of training and effective training modalities). Results: Of the 78 respondents (23% response rate), the mean age was 41-42 (range 26-67) and the majority were female (53%). Fifty-seven percent of the respondents had completed residency at the time of participation and approximately two-thirds were board certified. The majority of respondents were in the field of internal medicine (61%). Overall, participants felt fairly confident in their ability to help patients and their families with end-of-life issues and care and found most methods of end-of-life training useful. Discussion: Despite educational initiatives and recommendations by various oversight, evaluation and licensing committees, paucity of end-of-life training pervades not only undergraduate medical education, but also residency training and beyond. Based on our review of the literature, our results appears to convey a disconnect between physician's perceived abilities in end-of-life care and what may be happening in the field. This study helps to describe practitioners' personal attitudes regarding their ability to deliver end-of-life care as a measure of self-efficacy and how this measure varies by demographic factors. In addition, it lends some insight into the practitioners' needs and priorities with respect to end-of-life education and training.